2011
DOI: 10.1016/j.indmarman.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of market orientation on the development of relational capabilities and performance outcomes: The case of Russian industrial firms

Abstract: The article investigates the role of market orientation as an antecedent for the development of relational capabilities and performance in Russian industrial firms. We test the direct role of different aspects of market orientation on business performance in comparison to an indirect and mediated influence via improving a firm's ability to become embedded in relational structures. The results of an empirical study demonstrate the differential impact of components of market orientation -customer orientation, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
109
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 98 publications
(174 reference statements)
14
109
0
9
Order By: Relevance
“…Rodríguez-Díaz and Espino-Rodríguez [2006] found that interactions with business partners can provide firms with competitive advantages. These results are consistent with those of Smirnova et al [2011] who suggest that the existence of relational capabilities enhances competitive advantages of firms [cited in Kenny, 2009, p. 151]. Similarly, the findings of Dyer and Singh [1998] indicate that relational capabilities and firm performance are significantly and positively related, i.e.…”
Section: Tie Strength -The Nature Of Relationshipssupporting
confidence: 89%
“…Rodríguez-Díaz and Espino-Rodríguez [2006] found that interactions with business partners can provide firms with competitive advantages. These results are consistent with those of Smirnova et al [2011] who suggest that the existence of relational capabilities enhances competitive advantages of firms [cited in Kenny, 2009, p. 151]. Similarly, the findings of Dyer and Singh [1998] indicate that relational capabilities and firm performance are significantly and positively related, i.e.…”
Section: Tie Strength -The Nature Of Relationshipssupporting
confidence: 89%
“…Relasional jejaring entrepreneur berpengaruh pada kinerja bisnis. Hasil penelitian konsisten dengan penelitian Biggs dan Shah (20060, Watson (2007), Smirnova et al,(2011), Zohdi et al,(2013) maupun Meihua dan Jianhui (2015). Relasional jejaring akan menciptakan sinergi dengan pihakpihak terkait dan memberi akses untuk mendapatkan sumber daya eksternal yang dibutuhkan sehingga akan meningkatkan kinerja perusahaan.…”
Section: Kesimpulanunclassified
“…Hortinha et al (2011) observed a positive relationship between market orientation and business performance. Researchers such as: Kohli and Jaworski (1996;Slater and Narver, 1994;Lado and Maydeu-Olivares, 2001;Yoon and Lee, 2005;Lai et al, 2009;Mahmoud et al, 2010;Smirnova et al, 2011;Bahman and Mehdi, 2011;Mashahadia et al, 2016) have all observed a positive relationship between market orientation and business performance. According to Herhausen (2016) market orientation has an incremental positive effect on business performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The execution of a suitable marketing activity promotes superiority of a firm's activities and strengthens the competiveness and market share of the firm (Ghouri et al, 2011). It therefore becomes ruinous for organizations to ignore the consequence of market oriented activities in their business setup (Salminen, 2006;Smirnova et al, 2011;Theodosiou et al, 2012). The difficulty in assessing marketing performance stems from the fact that, its measurement is basically depended on external irrepressible factors such as customers and competitors (Neely, 2002).…”
Section: Introductionmentioning
confidence: 99%